Anthropogenic Effects on Surface Water Quality Assessment in Baitarani River Basin, Odisha Using GIS and MCDM Techniques - Das, Abhijeet (Engineering Research Transcripts, 2023)
Surface water is necessary for the sustainable expansion of society, economy, and agriculture in and around Baitarani Basin, Odisha. 22 significant surface water regulating variables were collected from 13 locations during the 5-year (2018-2023) monsoon period and were, developed by combining entropy-based water quality index (EWQI) data and TOPSIS analysis was carried out to determine surface water prospect zones. The selected catchments and its spatial maps were designated and the anticipated surface water zone model's results were divided into four groups: excellent (15.38%), good (38.46%), medium (15.3%) and poor (30.77%). However, TOPSIS, a multi-objective judgement tool, was used to rank the sites based on their relative emissions of harmful pollutants. Findings suggest that St-8 obtained the highest performance score and was recognized, as perhaps, the most polluted location in comparison to other remaining sites. Urbanization, irrigation, landfills, and e-waste are the primary agents for water quality deterioration. Chemical indices such as SAR, RSC, MH, KI, PS, PI, CR, CAI-1, and CAI-2, were evaluated and the results demonstrated that the river is good for irrigation. USSL diagrams categorized the water samples as C1-S1 and C2-S1, respectively, which promotes irrigation suitability. From the Piper and Durov diagram plots, two different types of water were identified as Na+-Cl- and Ca (HCO3)2. On the other hand, Gibb’s plot implies that most samples fall under the evaporation-precipitation dominance.